PENGAMANAN PESAN TEKS MENGGUNAKAN KRIPTOFRAFI ALGORITMA VIGENERE CHIPER DARI SERANGAN EAVESDROPPING - Sihombing, Benyamin; Manrung, Dina Patresia Samuana; Ahadi, Eko; Gunawan, Indra (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
The development of information technology is increasing rapidly, increasingly in communication and information. People often travel data or information with the help of technology, one of which is by using text messages. Security is very necessary so that threats such as piracy or eavesdropping on a message can prevent and not involve the parties concerned. Many attacks occur such as eavesdropping attacks that leak messages or information, but this can be overcome by using the vigenere cipher algorithm. This vigenere cipher cryptographic algorithm uses encryption and description processes to permit confidentiality of messages.